2017
DOI: 10.1016/j.cmi.2016.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Low and disparate seroprotection after pentavalent childhood vaccination in the Lao People's Democratic Republic: a cross-sectional study

Abstract: After a full documented course of vaccination, seroprotective rates were unusually low and disparate against components of the pentavalent vaccine. These can only partially be explained by the negative predictors identified. Although many children had been infected, only few were chronic carriers of HBsAg. Our study demonstrates an urgent need to monitor the serologic response to vaccination, particularly in resource-poor countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 23 publications
6
33
0
Order By: Relevance
“…Specifically compared with previous studies conducted in Lao PDR, such as Huaphan, a serologic investigation that used non-random sampling of participants with at least 3 documented HBV vaccinations revealed that 17.0% (15/55) were serologically protected (> 10 mIU/mL by serum) at the age of 1–4 years [18]. Another study with 3 documented DTP-Hepatitis B-Hib vaccinations in Vientiane, Khammouane, and Boulhikhamxay provinces in Lao PDR revealed 37.9% (394/1039) of participants were serologically protected (> 10 mIU/mL by serum) at the age of 9–50 months [19]. Thus, unexpectedly low seropositive rates were found among Laotian children with a documented vaccination history in both of these serologic studies [18, 19] nearly as bad as in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically compared with previous studies conducted in Lao PDR, such as Huaphan, a serologic investigation that used non-random sampling of participants with at least 3 documented HBV vaccinations revealed that 17.0% (15/55) were serologically protected (> 10 mIU/mL by serum) at the age of 1–4 years [18]. Another study with 3 documented DTP-Hepatitis B-Hib vaccinations in Vientiane, Khammouane, and Boulhikhamxay provinces in Lao PDR revealed 37.9% (394/1039) of participants were serologically protected (> 10 mIU/mL by serum) at the age of 9–50 months [19]. Thus, unexpectedly low seropositive rates were found among Laotian children with a documented vaccination history in both of these serologic studies [18, 19] nearly as bad as in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Another study with 3 documented DTP-Hepatitis B-Hib vaccinations in Vientiane, Khammouane, and Boulhikhamxay provinces in Lao PDR revealed 37.9% (394/1039) of participants were serologically protected (> 10 mIU/mL by serum) at the age of 9–50 months [19]. Thus, unexpectedly low seropositive rates were found among Laotian children with a documented vaccination history in both of these serologic studies [18, 19] nearly as bad as in our study. Our extremely low rate relative to these two studies may be because we investigated a random sample of children, whereas the two previous serologic investigations investigated non-randomized population samples as well as had differences in study design and methodology, and may also reflect the reality of the situation in hard-to-reach areas where observed cold chain problems can result in inactive vaccine immunization.…”
Section: Discussionmentioning
confidence: 99%
“…Despite improvements in healthcare in the Lao People’s Democratic Republic (PDR), the incidence of vaccine-preventable diseases remains high. Vaccination represents one of the most important public health interventions [1–3], but many children fail to respond to the pentavalent diphtheria-tetanus-pertussis (whole cell)–Hepatitis B– Haemophilus influenzae type B vaccine (DTPw-HepB-Hib) vaccine [4], which is scheduled at 6, 10, and 14 weeks after birth. A first dose against hepatitis B is given as a monovalent vaccine within 24 hours after birth (“birth dose”).…”
mentioning
confidence: 99%
“…Other reasons, in addition to age at the time of vaccination, whereby children vaccinated at born showed titers between 1 and 9.99 mIU/mL could be an incomplete vaccination schedule or the application of a pentavalent vaccine formulation, which may induce low and uneven aHBs titers [18].…”
Section: Discussionmentioning
confidence: 99%